2016
DOI: 10.1038/nature18324
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric coupling from G protein to the agonist-binding pocket in GPCRs

Abstract: G protein-coupled receptors (GPCRs) remain the primary conduit by which cells detect environmental stimuli and communicate with each other1. Upon activation by extracellular agonists, these seven transmembrane domain (7TM)-containing receptors interact with heterotrimeric G proteins to regulate downstream second messenger and/or protein kinase cascades1. Crystallographic evidence from a prototypic GPCR, the β2-adrenergic receptor (β2AR), in complex with its cognate G protein, Gs, has provided a model for how a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
235
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(269 citation statements)
references
References 32 publications
29
235
4
1
Order By: Relevance
“…We have captured both dissociation and binding of an orthosteric ligand in a single all-atom GPCR simulation in the case of ARC binding to the M 2 receptor. These results are consistent with the recent experimental finding that the G-protein mimetic nanobody stabilizes a closed receptor conformation and dramatically affects the association and dissociation of GPCR ligands (17). Notably, Dror et al (23) successfully observed both binding and dissociation of allosteric modulators at the M 2 receptor through long-timescale conventional MD (cMD) simulations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We have captured both dissociation and binding of an orthosteric ligand in a single all-atom GPCR simulation in the case of ARC binding to the M 2 receptor. These results are consistent with the recent experimental finding that the G-protein mimetic nanobody stabilizes a closed receptor conformation and dramatically affects the association and dissociation of GPCR ligands (17). Notably, Dror et al (23) successfully observed both binding and dissociation of allosteric modulators at the M 2 receptor through long-timescale conventional MD (cMD) simulations.…”
Section: Discussionsupporting
confidence: 80%
“…Coupling of the receptor with the G protein or mimetic nanobody typically increases agonist binding affinities (17). However, structural information of partial agonist binding is scarce, except for few other GPCRs (18).…”
mentioning
confidence: 99%
“…Conformational selectionbased ligand-binding mechanisms as well as multiple receptor signaling states are well documented for other GPCRs, including the B2AR and CB1 receptor (7,20,(35)(36)(37)(38). Hence, the delayed reversion to the inactive receptor conformation we observe for rhodopsin might play a heretofore unappreciated role here and in other GPCR signaling systems.…”
Section: After Rhodopsin Photoactivation An Equilibrium Of Atr Releamentioning
confidence: 91%
“…For example, addition of an extracellular agonist to β 2 AR results in conformational changes at the intracellular ends of receptor TM helices (45, 71, 107), and enhances the stability of receptor:G protein complexes (144) (“upside-down”). On the other hand, addition of either G protein or a G protein-mimicking nanobody Nb80 (124), both of which bind intracellularly, affects affinity and binding kinetics of extracellular agonists (30, 107) (“downside-up”). The bi-directional communication works not only in the context of receptor activation, but also in inactivation: inactive-state-specific intracellularly-binding nanobodies and antibodies reduce receptor affinity for extracellular agonists and increase affinity for inverse agonists (52, 123).…”
Section: On Allostery Of Chemokine Receptorsmentioning
confidence: 99%